101k views
12 votes
Need help to do this step by step please
3x2 - 2x=-1

User Vbyec
by
4.5k points

1 Answer

5 votes

Answer:

Solving the expression
3x^2-2x=-1 we get:
\mathbf{x=(1+√(2)i )/(3)\:or\:x=(1-√(2)i )/(3)}

Explanation:

We need to solve the expression:
3x^2-2x=-1

This is a quadratic expression and it can be solved using quadratic formula

Solving:


3x^2-2x=-1\\

we can write it as:


3x^2-2x+1=0

The quadratic formula is:
x=(-b\pm√(b^2-4ac))/(2a)

where a = 3, b = -2 and c= 1

Putting values and solving:


x=(-b\pm√(b^2-4ac))/(2a)\\x=(-(-2)\pm√((-2)^2-4(3)(1)))/(2(3))\\x=(2\pm√(4-12))/(2(3))\\x=(2\pm√(-8))/(6)\\We\:know\:that\:√(-1)=i\\x=(2\pm√(8)√(-1) )/(6) \\We\:know\:√(8)=√(2* 2 * 2)=√(2^2 * 2)=2√(2) \\x=(2\pm2√(2)i )/(6)\\Now,\\x=(2+2√(2)i )/(6)\:or\:x=(2-2√(2)i )/(6)\\x=(2(1+√(2)i) )/(6)\:or\:x=(2(1-√(2)i) )/(6)\\x=(1+√(2)i )/(3)\:or\:x=(1-√(2)i )/(3)

So, solving the expression
3x^2-2x=-1 we get:
\mathbf{x=(1+√(2)i )/(3)\:or\:x=(1-√(2)i )/(3)}

User Fabian Braun
by
4.1k points